Examining the Effectiveness of Metacognitive Therapy on Self-Disclosure and Self-Restraint in Single Women Unwilling to Marry - Sistani , Fahimeh; Khayatan, Felor; Yousefi , Zahra (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to examine the effectiveness of metacognitive therapy on self-disclosure and self-restraint in single women unwilling to marry. The research method was quasi-experimental, employing a pre-test–post-test and follow-up design with a control group. The statistical population consisted of all female students at Islamic Azad Universities in Isfahan during the 2022–2023 academic year. Participants were selected based on inclusion and exclusion criteria. A total of 30 individuals were selected through purposive sampling and were randomly assigned to the experimental and control groups (15 participants in each group). Both groups completed the pre-test, after which the experimental group received metacognitive therapy over the course of eight intervention sessions, whereas the control group received no intervention. Data were collected using the 24-item Emotional Self-Disclosure Questionnaire by Snell et al. (1988), the 30-item Self-Restraint Questionnaire by Weinberger and Schwartz (1990), and the Marriage Inclination Scale by Heydari et al. (2004). Data analysis was conducted using repeated measures analysis of variance in SPSS version 23. The findings indicated that metacognitive therapy led to increased self-disclosure and self-restraint in single women unwilling to marry, and the therapeutic effects persisted at the follow-up stage (F = 9.95, p < .01). Based on the present findings, metacognitive therapy can be utilized to enhance self-disclosure and self-restraint in single women unwilling to marry.